Complete rehabilitation using a digital smile design combined with conventional restorative materials and CAD/CAM in bruxism patient - Eri Hendra Jubhari; Nur Aenun (Makassar Dental Journal PDGI Makassar, 2020)
The development of aesthetic rehabilitation techniques in the field of dentistry has resulted in a paradigm shift in the field of restoration and aesthetics. Dentists plan care for patients need to do a good analysis, not only thinking about the treatment of one tooth but on all teeth that interfere with aesthetics when the patient smiles, especially for patients with bruxism and very worn teeth. A dentist must be able to choose treatments that are appropriate to the situation and condition of the patient. A di-gital smile design is used to formulate an overall mouth rehabilitation treatment plan using a combination of materials and conventional and digital methods. The different strengths of conventional and digital methods, make the combination of these two methods an adequate choice and represent the best part of both methods in contemporary dental practice. In the selection of restorative material in patients with bruxism and very worn teeth, the dentist must consider the patient's dental wear.